Analisis Upaya Pematahan Dormansi Biji Andaliman (Zanthoxylum acanthopodium DC.) dengan Pelukaan dan Perendaman Air Kelapa - Widya Fransiska; Sujarwati Sujarwati (JOSTECH Journal of Science and Technology, 2023)
Andaliman fruit is a typical food source for the Batak tribe and is usually used as a cooking spice under the name "Batak pepper". The fruit used as a spice in cooking is young fruit. This study aims to determine the effect of seed selection by injury on andaliman seed germination, determine the effect of concentration and duration of soaking seeds in coconut water on andaliman seed germination. This study used a Factorial Completely Randomized Design (RALF) with two factors. The fisrt factor is the concentration of coconut water 0%, 50%, 100%. The second factor is the length of immersion time of 12 hours and 24 hours. Parameters observed were germination percentage, vigor index, seed germination time. The results of this study showed that seed selection by wounding and soaking coconut water could not break the dormancy of andaliman seeds. No seeds germinated until 45 DAP. Seed conditions at 45 DAP were 76-88% whole seeds, 4-16% slimy seeds and 4-16% moldy seeds